2005
DOI: 10.1002/app.21684
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the water selectivity of ULTEM poly(ether imide) pervaporation films by an allylamine‐plasma‐polymerized layer

Abstract: ABSTRACT:The wettability and surface energy of extruded ULTEM poly(ether imide) films strongly increased (the water contact angle varied from 75 to 38°and the surface energy varied from 45.3 to 59.5 mJ m Ϫ2 , respectively) with the deposition of an allylamine-plasma-polymerized layer and were characterized with X-ray photoelectron spectroscopy, scanning electron microscopy, and atomic force microscopy according to the experimental parameters. Pervaporation tests for dehydrating the water/ethanol azeotropic mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…For instance, the surface modification of poly(dimethylsiloxane) (PDMS) membranes with no change in their inner structure can control the selectivity of the solution process without changing the diffusion process [31]. The allylamine-plasma surface-modified PEI membrane was shown to exhibit a higher separation factor, but there was no significant difference in permeate flux between untreated and treated PEI membranes [12]. Therefore, our results that the flux with operating time shows a similar changing trend no matter what side is in contact with the feed are readily understood because there is no change in their inner structures.…”
Section: Surface Reconstruction During Pervaporationmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, the surface modification of poly(dimethylsiloxane) (PDMS) membranes with no change in their inner structure can control the selectivity of the solution process without changing the diffusion process [31]. The allylamine-plasma surface-modified PEI membrane was shown to exhibit a higher separation factor, but there was no significant difference in permeate flux between untreated and treated PEI membranes [12]. Therefore, our results that the flux with operating time shows a similar changing trend no matter what side is in contact with the feed are readily understood because there is no change in their inner structures.…”
Section: Surface Reconstruction During Pervaporationmentioning
confidence: 96%
“…For example, H 2 O wt% in the permeation through poly(vinyl alcohol) (PVA) membrane treated with allyl alcohol plasma first increased, and finally attained equilibrium as the pervaporation process proceeded [8]. When the poly(ether imide) (PEI) membrane deposed an allylamineplasma-polymerized layer employed to dehydrate the water/ethanol azeotropic mixture, its selectivity toward water increased from 2000 to 10,850, while the total flux decreased from 3 to 2.6 g/m 2 h after about 30 h of operation [12]. The reason for such time-dependent properties of pervaporation performance was debatable.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the apparent N 1s peak ( Figure 3) is broadened and shifted from a higher binding energy (attributed to NOCAO groups, about 400 eV) to a lower binding energy (attributed to CON groups, about 399 eV), which implies the formation of amide. 13 On the basis of FTIR and XPS results, a reaction mechanism is proposed in Figure 4, which is similar to the crosslinking of 6FDA-polyimde 17 and Matrimid ® . 18 XRD spectra as shown in Figure 5 reveal that the peaks gradually shift to the right after crosslinking, indicating the d-space decreases significantly.…”
mentioning
confidence: 97%
“…Plasma treatment is another way to modify the properties of polyimide. Kaba et al 13 found that the wettability of polyetherimide (PEI) dense films and the selectivity of the membrane can be significantly improved by the anallylamineplasma polymerized layer for the dehydration of ethanol. Crosslinking modification of polyimide has been extensively studied in the preparation of gas separation membranes; however, the crosslinking modification of polyimide is seldom used for pervaporation dehydration.…”
mentioning
confidence: 99%